The epidemiology of schizophrenia - Murray, Robin 1944- (Cambridge University Press, 2003)
An international team of leading researchers and clinicians here provide a comprehensive, epidemiological overview of this multi-faceted and still perplexing disorder, and address some of the key questions it raises. How important in the genetic contribution to schizophrenia? Do pregnancy and birth complications increase the risk for schizophrenia? Is the incidence of schizophrenia changing? Why is the rate higher among immigrants and in those born in cities? Controversial issues such as the validity of discrete or dimensional classifications of schizophrenia and the continuum between psychosis and 'normality' are explored in depth, and separate chapters are devoted to topics of particular relevance to schizophrenia such as suicide, violence and substance abuse. Finally, new prospects for treatment and prevention are considered. Drawing together the findings from social, genetic, developmental and classical epidemiology of schizophrenia, this text will prove an invaluable resource for clinicians and researchers